A combined experimental and computational study of NHC-catalyzed allylation of allenoate with MBH esters: new regiospecific and stereoselective access to 1, 5-enyne. Issue 1 (16th November 2021) - Sun, Fang; Lu, Fangfang; Song, Xue; Wu, Wenchao; Zhang, Kai; Yu, Chenxia; Li, Tuanjie; Wei, Donghui; Yao, Changsheng
Abstract : An NHC-catalyzed regiospecific allylation of α-substituted allenoates with MBH carbonates derived from aryl aldehyde furnished highly functionalized 1, 5-enynes. Abstract : An NHC-catalyzed regiospecific allylation of α-substituted allenoates with MBH carbonates derived from aryl aldehyde furnished highly functionalized 1, 5-enynes bearing a quaternary carbon successfully. Combining with DFT calculations, the reaction mechanism of this conversion was proposed. This method has the advantages of high regioselectivity, good yields and mild reaction conditions. This transformation not only provided a new access to 1, 5-enyne, but also enriched the chemistry of allenoates and NHC catalysis.